Systematic Review and Meta-Analysis of Candidate Gene Association Studies With Fracture Risk in Physically Active Participants - Ryan-Moore, Edward; Mavrommatis, Yiannis; Waldron, Mark (Frontiers in Genetics, 2020)
Background: Fractures are common in physically active populations and genetic differences may mediate injury risk. Objective: To meta-analyse the pooled results of candidate gene association studies with non-osteoporotic fracture risk in physically active humans. Methods: Systematic searching of databases returned 11 eligible studies published in English. Pooled odds ratios (ORs) with 95% confidence intervals (CI) were produced using allele contrast, recessive and homozygote contrast meta-analysis models to evaluate associations of risk alleles in the COL1A1 (rs1800012), COL2A1 (rs412777), CTR (rs1801197), ESR1 (rs2234693 & rs9340799) LRP5 (rs3736228), VDR (rs10735810, rs7975232, rs1544410 & rs731236) genes with fracture incidence. Results: Eligible study quality was generally low (7/11) and no significant overall effect was found for any genetic variant with any comparison model (p >0.05). A trivial reduction in fracture risk was found for female participants with the COL1A1 Sp1 (rs1800012) T allele (OR = 0.48, 95% CI = 0.25 – 0.91, p = 0.03, d = -0.18). Conclusions: No overall effect was found from the pooled results of included genetic variants on fracture risk in physically active participants. The COL1A1 Sp1 rs1800012 T allele may reduce fracture risk in physically active females but further high-quality research with sex-specific analysis is required. Trial Registration: (PROSPERO; CRD42018115008).